2007
DOI: 10.1158/1535-7163.mct-06-0604
|View full text |Cite
|
Sign up to set email alerts
|

Target-specific cytotoxic activity of recombinant immunotoxin scFv(MUC1)-ETA on breast carcinoma cells and primary breast tumors

Abstract: MUC1 is a mucin family protein, overexpressed in more than 90% of breast cancers in an underglycosylated form, exposing the core peptides of the extracellular domain that act as a potential target for antibody-mediated therapy. We have developed an anti-MUC1 scFv antibody from a phage library of mice immunized with synthetic peptide MUC1-variable number of tandem repeats. MUC1 binding phages were affinity selected through biopanning using a biotin-streptavidin pull-down method. The selected phage clones showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Wels et al (1995) also reported that toxin sensitivity of the ErbB-2-specific scFv(FRP5)-ETA depended more on the mechanism of internalization and intracellular processing of the immunotoxin rather than its binding to ErbB-2 and epidermal growth factor receptor on the membrane. The discordance of cytotoxicity with the levels of receptor expression on the cell lines has been observed earlier (Kihara and Pastan 1995;Singh et al 2007) highlighting that cytotoxic killing depended more on the above factors rather than the binding of DT-SCF or SCF-ETA' to c-kit receptor on the membrane. Lower IC 50 values for IMR-32 might also be attributable to the same mechanism.…”
Section: Discussionsupporting
confidence: 56%
“…Wels et al (1995) also reported that toxin sensitivity of the ErbB-2-specific scFv(FRP5)-ETA depended more on the mechanism of internalization and intracellular processing of the immunotoxin rather than its binding to ErbB-2 and epidermal growth factor receptor on the membrane. The discordance of cytotoxicity with the levels of receptor expression on the cell lines has been observed earlier (Kihara and Pastan 1995;Singh et al 2007) highlighting that cytotoxic killing depended more on the above factors rather than the binding of DT-SCF or SCF-ETA' to c-kit receptor on the membrane. Lower IC 50 values for IMR-32 might also be attributable to the same mechanism.…”
Section: Discussionsupporting
confidence: 56%
“…The cytotoxic activity was also evident in primary breast tumors. 73 In conclusion, MUC1 has all the potential to be used as a target for the site specific delivery of therapeutic agents, as a vaccine against MUC1 expressing cancers and also as an excellent immunomoduator. …”
Section: Advancement Of Immunotherapeutic Applications With Muc1mentioning
confidence: 98%
“…Other groups have previously reported on scFv-ETA'-fusion immunotoxins of similar format specific for CD22, CD25, CD7, CD64, CD33, CD19 and more antigens for the treatment of hematological malignancies [25,26,32,46,37,38] and others, specific for the Lewis Y antigen, IL-13, the EGF-receptor, ErbB2/HER2, EpCAM, and MUC1 for the treatment of solid tumors [33,29,34,2,13,40]. These scFv-ETA' immunotoxins have not yet been approved for routine clinical use, but in preclinical and early-stage clinical studies they have demonstrated encouraging results.…”
Section: Introductionmentioning
confidence: 99%